Thermal Sensitive Quantum and Phonon Confinement in Semiconducting Triangular-Shaped MoS2 - Majee B.P.; Gupta J.D.; Sanskrityayn A.; Mishra A.K. (My University, 2025)
Monolayer MoS2 and few-layer MoS2 have been widely studied fundamentally, and for application purposes, however, less investigated bilayer or trilayer MoS2 may demonstrate properties at the interface of monolayer and few-layer MoS2. Here, we study the physical properties of bilayer MoS2 with a triangular shape, prepared over a SiO2/Si substrate via a chemical vapor deposition method. We analyze the thermal sensitive quantum confinement behavior of bilayer MoS2 by a temperature-dependent photoluminescence study to understand its semiconducting nature. We also examine the phonon confinement behavior and its thermal response for bilayer MoS2, which can play a key role in the performance and thermal management of MoS2-based optoelectronic devices. The optothermal Raman technique has been used to measure the thermal behavior of the prepared MoS2 over the SiO2/Si substrate. We obtain interfacial thermal conductance and thermal conductivity at room temperature for supported bilayer MoS2 to be around 1.264 ± 0.128 MW m-2 K-1 and 42 ± 8 W m-1 K-1, respectively, suggesting its suitability for thermal management in optoelectronic devices. © 2021 American Chemical Society.